Mayan cities of Yucatan : settlement patterns and structure types - Lipovac, Nenad (Array, 2018)
The research results on prehistoric Mesoamerican settlements in Mexico are presented through the planners’, rather than the archeological, point of view. Numerous settlement types and sizes were analyzed by comparing the archeological data and the personal experience gained during the research in situ. Even though the cities were unplanned, derived results proved the astonishingly high level in the construction of structures and buildings in relation to astronomical phenomena.